Sociocultural Dynamics of Islamic Legal Reform Across Muslim-Majority Countries: A Comparative Perspective - Ahmad, Mansur; Wathoni, Lalu Muhammad Nurul; Sainun; Saidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: Islamic law exists in a fluid and contentious realm inside modern Muslim-majority states, where its application embodies both theological beliefs and sociopolitical frameworks, as well as cultural perceptions. Purpose: This study seeks to evaluate the sociological elements affecting the implementation of Islamic law in Indonesia, Brunei Darussalam, and Saudi Arabia, emphasizing the roles of legal pluralism, state ideology, and religious authority in its enforcement Methods: The study employs a qualitative-comparative methodology, utilizing document analysis and secondary data review to examine the historical evolution, legal frameworks, and sociocultural contexts that support Islamic law in the three nations Results: The findings indicate that Brunei and Saudi Arabia implement Islamic law inside monarchical and theocratic structures, but Indonesia reconciles Islamic principles within a pluralistic legal framework shaped by democracy, adat, and secular constitutionalism Implication: This article theoretically enhances Islamic legal scholarship by contextualizing Islamic law within sociological and reception-focused frameworks, demonstrating that its legitimacy arises from intricate interactions among tradition, state, and society. The research provides insights for policymakers to formulate context-specific legal reforms that take into account normative Islamic ideals and varied sociocultural situations. Originality: Sociological perspective and cross-regional analysis, which transforms the discussion of Islamic law from strict doctrinarism to fluid social practice within the worldwide Muslim community